2006
DOI: 10.1021/ja0552139
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Molecular Wires with Conjugated Bridging Ligands:  Onset of Band Formation in Linear Inorganic Conjugated Oligomers

Abstract: We have prepared and characterized a series of multimetallic oligomers of Ru using the pi-conjugated bridging ligand tetra-2-pyridyl-1,4-pyrazine (tppz), as well as mixed-ligand complexes with terpyridine end caps, and analyzed their electrochemical and spectroscopic properties, comparing them with modern computational electronic structure methods. The results suggest that the high degree of metal-metal interunit communication in these linear oligomers yields low HOMO-LUMO gaps, high delocalization, and the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 75 publications
2
56
0
5
Order By: Relevance
“…Binuclear complexes of 1-7 were prepared by reacting ferrocenylethynyl spacers (8)(9)(10)(11)(12) with stoichiometric amount of (g 5 -C 5 H 5 )(dppe)MCl. Complexes were purified by column chromatography and recrystallization.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Binuclear complexes of 1-7 were prepared by reacting ferrocenylethynyl spacers (8)(9)(10)(11)(12) with stoichiometric amount of (g 5 -C 5 H 5 )(dppe)MCl. Complexes were purified by column chromatography and recrystallization.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Recently, the study of homo-and hetero-metallic binuclear transition metal complexes in which the end-capped metal centers are connected by p-conjugated organic linear spacers has been an intriguing area of research, since such system may provide the possibility to study the electronic coupling between the redox-active end-capped metal centers, or propose as models for molecular wires. In this context, end-capping of unsaturated organic spacers with various redox-active groups, such as ferrocene, ruthenium(II) polypyridine [4][5][6][7][8][9], [RuL 2 Cl] (L 2 = 2PPh 3 , Ph 2 PCH 2 CH 2 PPh 2 (dppe)) [10,11], and [M(g 5 -C 5 H 5 )L 2 ] (M = Fe(II), Ru(II), and Os(II)) metal centers [12][13][14][15][16][17][18][19][20][21], have been most studied where they are intended to promote the long-range electronic coupling. The nature of the end-capped metal center and p-conjugated organic spacer plays significantly important role in determining the magnitude of electronic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this particular system because it was used in previous conductance measurements 22,23 as a monomer of chains -albeit with different anchor groups -where it was found that depending on the chain length either coherent transport or electron hopping is observed 22 . In addition spectroscopic and quantum chemical studies on similar Ru complexes [24][25][26][27][28] suggest that this molecular species offers the possibility to easily link two carbon-rich chains to each other for the formation of reversible redox systems [29][30][31] with distinct optical transition properties 32,33 , thereby serving as a starting point for the investigation of chains with multiple redox active centers 27 . In contrast to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…the greater the difference, the greater the electron communication between the metal centers. [43][44][45] This parameter allows, also, the evaluation of the stabilization or destabilization of the metal π orbitals (t 2g ) by coordination to a second metal unit. Such change could be dictated by variations in the π-accepting ability of the bridge, which can be modulated by the size, degree of conjugation, and conformational aspects.…”
Section: Resultsmentioning
confidence: 99%